Protection of Copyright for Derivative Works of Fanfiction Without Permission - Harbelubun, Jenica Chechilia; Akyuwen, Rory Jeff; Labetubun, Muchtar Anshary Hamid (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Copyright holders have exclusive rights to determine the use of their work. Fanfiction is often considered a derivative work that requires permission from the original creator, but many are made without permission, thus violating copyright.Purposes of the Research: To find out and discuss the form of protection of the creator's moral rights against fanfiction works without permission and legal remedies for copyright infringement.Methods of the Research: Normative legal research methods with a statutory approach, case approach and conceptual approach, to answer the problems raised.Findings of the Research: Legal protection of the moral rights of creators against a derivative fanfiction work without permission can be done preventively or repressively, with the repressive approach being considered more effective. Legal efforts can be taken through litigation (civil and criminal lawsuits) and non-litigation (mediation, licensing agreements, or closing online content).